RANCANG BANGUN ALAT SCALING PORTABEL UNTUK MENURUNKAN WAKTU DOWNTIME PADA DIES TIPE M DI PT. GZB - Nursim; Ariansyah, Ferdhika (Technologic, 2024)
GZB is a manufacturing company engaged in the two-wheeled automotive sector, whose production process includes various processes such as casting, plastic injection, machining, assembling, painting steel, painting plastic, press, welding, and final inspection. In the production process, the company has potential losses in production such as potential reject parts and lost production time, which should not be included in the company's production target. Researchers make observations and genba in the field to analyze the causes of production lost time and reject parts, especially in the casting section. Lost production time is the main focus of this research because this has an impact on reject parts as well. The purpose of this research is to find the right solution to reduce production lost time caused by downtime maintenance dies. A solution for making a portable scaling tool was found because this solution was the best choice in terms of time availability, human resources, and researcher analysis. This tool is designed to be portable so that it can be easily moved and used in hard-to-reach places. The research method used is 8 steps with the support of 7 tools. Tests were carried out on Type M dies. The test results showed that using this portable scaling tool can significantly reduce downtime. This tool has the potential to increase operational efficiency and productivity. Keywords: Portable Scaling Tool, Casting, Downtime, Eight Steps and Seven Tools, Production Lost Time.